Perda da integridade mucosa laríngea in vitro induzida por solução ácida contendo ácido biliar em camundongos: efeito protetor da goma de cajueiro - Borsaro, Aline Almeida Figueiredo (2017)
Laryngopharyngeal reflux disease (LPR) is an extraesophageal manifestation of gastroesophageal reflux disease (GERD). Despite the high prevalence and impact, there is no consensus concerning its pathophysiology, diagnosis and treatment. OBJECTIVE: This study aims to evaluate the effect of acid solutions associated with pepsin and/or bile acid on the transepithelial electrical resistance (TEER), transepithelial permeability, gene expression of epithelial junction proteins and proteins of the apoptotic pathway in laryngeal mucosa and to investigate a possible topic protective effect of cashew gum in these changes. METHODS: Murine larynges were exposed to contact with different solutions containing pepsin and bile acid at different pH and TEER was measured by Ussing chamber apparatus. Subsequently, we measured the effect of a weakly acidic solution (pH 5) containing pepsin or bile acids (in different concentrations and types) on laryngeal TEER. Then, it was determined the effect of a weakly acid solution (pH 5) containing taurodeoxycholic acid (TDCA) in transepithelial laryngeal permeability to fluorescein and gene expression of junction proteins and proteins of the apoptotic pathway by PCR and, finally, it was evaluated a possible topic protective effect of 10% cashew gum in these changes. RESULTS: It was observed that the decrease in the laryngeal TEER depends on the pH, when using solution containing pepsin and bile acid, but it still drops with pH 5. The exposure of the laryngeal mucosa to the solution at pH 5 containing bile acid, despite the presence of pepsin, promoted a decrease in laryngeal TEER. The challenge with bile acid in solution at pH 5 in the larynx increased transepithelial permeability and caused upregulation of gene expression of junctional complex proteins associated with an increase of gene expression of pro apoptotic proteins. Finally, the preventive effect of CG was detected in the reduction of TEER and in the increase of laryngeal transepithelial permeability. CONCLUSIONS: We can suggest that weakly acidic solutions in the presence of bile acids trigger a loss of laryngeal epithelial barrier resulting from an impairment of epitelal junction proteins secondary to apoptosis and this may be protected by topical treatment. These findings can open new perspectives for the treatment of pharyngolaryngeal reflux disease. Keywords: Bile acid. Cashew gum. Laryngopharyngeal reflux. Gastroesophageal reflux.